Discovery of New Microneme Proteins in Cryptosporidium parvum and Implication of the Roles of a Rhomboid Membrane Protein (CpROM1) in Host–Parasite Interaction - Gao, Xin; Yin, Jigang; Wang, Dongqiang; Li, Xiaohui; Zhang, Ying; Wang, Chenchen; Zhang, Yuanyuan; Zhu, Guan (Frontiers in Veterinary Science, 2021)
Apicomplexan parasites possess several unique secretory organelles, including rhoptries, micronemes, and dense granules, which play critical roles in the invasion of host cells. The molecular content of these organelles and their biological roles have been well studied in Toxoplasma and Plasmodium, but are underappreciated in Cryptosporidium, which contains many parasites of medical and veterinary importance. Only four proteins have previously been identified or proposed to be located in micronemes, one of which, GP900, was confirmed using immunogold electron microscopy (IEM) to be present in the micronemes of intracellular merozoites. Here, we report on the discovery of four new microneme proteins (MICs) in the sporozoites of the zoonotic species C. parvum, identified using immunofluorescence assay (IFA). These proteins are encoded by cgd3_980, cgd1_3550, cgd1_3680, and cgd2_1590. The presence of the protein encoded by cgd3_980 in sporozoite micronemes was further confirmed using IEM. Cgd3_980 encodes one of the three C. parvum rhomboid peptidases (ROMs) and is thus designated CpROM1. IEM also confirmed the presence of CpROM1 in the micronemes of intracellular merozoites, parasitophorous vacuole membranes (PVM), and feeder organelles (FO). CpROM1 was enriched in the pellicles and concentrated at the host cell-parasite interface during the invasion of sporozoites and its subsequent transformation into trophozoites. CpROM1 transcript levels were also higher in oocysts and excysted sporozoites than in the intracellular parasite stages. These observations indicate that CpROM1, an intramembrane peptidase with membrane proteolytic activity, is involved in host-parasite interactions, including invasion and proteostasis of PVM and FO.